“House”advancement pedicle flap for moderate to severe anal stenosis following anorectal surgery: an analysis of 15 cases - Yang Yi; Zhi Jianwen; Li E; He Yinghua; Jia Fei; Wang Xiaofeng (结直肠肛门外科)
[Objectives] To investigate the clinical effectiveness of“House”advancement pedicle flap for moderate to severe anal stenosis following anorectal surgery. [Methods] This was a retrospective analysis of 15 patients with moderate to severe anal stenosis following anorectal surgery treated with "House" advancement pedicle flap at our department between January 2019 and May 2021. Surgical details and postoperative follow-up were recorded. [Results] Of the 15 patients, the mean (SD) duration of surgery was 83.7 (27.9) minutes; the mean (SD) time to the first postoperative bowel movement was 3.3 (1.0) days; the median duration of hospitalization was 10 (6, 12) days. Five patients experienced postoperative complications, including two wound dehiscence, one hematoma, one incision infection, and one flap necrosis. Wounds healed uneventfully in five patients after targeted treatment. Flap survived in all 15 patients. Patients were followed up postoperatively for a mean (SD) of 9.9 (5.2) months, and none had recurrence. [Conclusion] “House”advancement pedicle flap is a relatively simple and safe procedure for moderate to severe anal stenosis following anorectal surgery with a high success rate.